Site-Specific Conjugation of Cell Wall Polyrhamnose to Protein SpyAD Envisioning a Safe Universal Group A Streptococcal Vaccine. Issue 2 (29th June 2021) - Gao, Nina J.; Uchiyama, Satoshi; Pill, Lucy; Dahesh, Samira; Olson, Joshua; Bautista, Leslie; Maroju, Shilpa; Berges, Aym; Liu, Janet Z.; Zurich, Raymond H.; van Sorge, Nina M.; Fairman, Jeff; et al.
Abstract : Abstract: Development of an effective vaccine against the leading human bacterial pathogen group A Streptococcus (GAS) is a public health priority. The species defining group A cell wall carbohydrate (GAC, Lancefield antigen) can be engineered to remove its immunodominant N -acetylglucosamine (GlcNAc) side chain, implicated in provoking autoimmune cross-reactivity in rheumatic heart disease, leaving its polyrhamnose core (GAC PR ). Here we generate a novel protein conjugate of the GAC PR and test the utility of this conjugate antigen in active immunization. Instead of conjugation to a standard carrier protein, we selected SpyAD, a highly conserved GAS surface protein containing both B-cell and T-cell epitopes relevant to the bacterium that itself shows promise as a vaccine antigen. SpyAD was synthesized using the XpressTM cell-free protein expression system, incorporating a non-natural amino acid to which GAC PR was conjugated by site-specific click chemistry to yield high molecular mass SpyAD-GAC PR conjugates and avoid disruption of important T-cell and B-cell immunological epitopes. The conjugated SpyAD-GAC PR elicited antibodies that bound the surface of multiple GAS strains of diverse M types and promoted opsonophagocytic killing by human neutrophils. Active immunization of mice with a multivalent vaccine consisting of SpyAD-GAC PR, together with candidate vaccine antigens streptolysin O and C5a peptidase, protected against GAS challenge in a systemic infection model and localized skin infection model, without evidence of cross reactivity to human heart or brain tissue epitopes. This general approach may allow GAC to be safely and effectively included in future GAS subunit vaccine formulations with the goal of broad protection without autoreactivity.